Design of Freight Electric Locomotive Body Meeting TSI Requirements - Xiangshuai GU; Yu HE; Long LI; Wenhui YUAN (机车电传动)
To meet the requirements of TSI (Technical Specification for Interoperability)to freight electric locomotive, design of integral bearing and lightweight structure was adopted, and the structure of underframe and other components was optimized. The strength and crashworthiness were simulated by FEA software. Static load test for vehicle body structure were also conducted to demonstrate the conformity of strength requirements. The vehicle body structure and its accessories had passed the TSI certification and maintained safe operation since 2019.